TRI PUSAT PENDIDIKAN SEBAGAI UPAYA MEMPERKUAT PENDIDIKAN KARAKTER SISWA DI TAMAN MUDA IBU PAWIYATAN - Akbar Al Masjid; Ardian Arief; Arya Dani Setyawan; Rahayu Retnaningsih (Universitas Sarjanawiyata Tamansiswa, 2019)
Ki Hadjar Dewantara's teachings which have accumulated as Tamansiswa's teachings are so prerequisite for noble valuesÂ of manners. One of the teachings in the form of the concept of education formulated by Ki Hadjar Dewantara is the Three Education Centers as teacher saka strengthening character education for the younger generation. The purpose of this study was to describe the application of the Three Education Centers in Taman Muda Ibu Pawiyatan as an effort to strengthen student character education, and explain the supporting and inhibiting factors and describe the results of the implementation of the Three Education Centers. This research is a descriptive qualitative research with the subject of this study are residents of Pawiyatan Ibu Muda School in Yogyakarta, which is the center of elementary school students' education level. Data collection techniques used are observation of recording techniques, and in depth interview techniques. The data validity checking technique uses source triangulation techniques. This study has the benefit of implementing the concept of the Three Education Centers that become the school culture in Taman Muda Ibu Pawiyatan. In addition, the long-term benefits of this study, namely the concept of three education centers can be cultured and implemented holistically in every educational environment.